How is the Strategic Decision Making Related to the Survival of Sharia Hospitality in the Covid-19 Period? - Suwardono Harjanto, Riani Asri Laksmi, Untoro Wisnu, Suyono Joko (International Journal of Advanced Science and Technology, 2020)
This research aimed to find out whether the strategic decision-making process related to the survival of sharia hotels in the Covid-19 period is following Islamic law. The object of his research was a Syariah Hotel in Solo, which was observed during the Covid-19 period from March to May 2020 using a qualitative approach. It was found that strategic decisions related to survival were following the existing Islamic standards while applying the health protocols recommended by the Ministry of Health.